2001
DOI: 10.1161/hc4601.099468
|View full text |Cite
|
Sign up to set email alerts
|

Dispatcher-Assisted Cardiopulmonary Resuscitation and Survival in Cardiac Arrest

Abstract: Background-Early cardiopulmonary resuscitation (CPR) improves survival in out-of-hospital cardiac arrest, and dispatcher-delivered instruction in CPR can increase the proportion of arrest victims who receive bystander CPR before emergency medical service (EMS) arrival. However, little is known about the survival effectiveness of dispatcherdelivered telephone CPR instruction. Methods and Results-We evaluated a population-based cohort of EMS-attended adult cardiac arrests (nϭ7265) from 1983 through 2000 in King … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
153
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 359 publications
(160 citation statements)
references
References 25 publications
6
153
0
1
Order By: Relevance
“…With better implementation of the links of this chain, cardiac arrest survival can be improved. 6 Early and high quality cardiopulmonary resuscitation (CPR) has been shown to greatly improve the survival rate of cardiac arrest victims, 7,8 as indicated by American Heart Association (AHA) guidelines changes from 2005 to date. [9][10][11] For this reason, the 2015 Guidelines for Cardiopulmonary Resuscitation stress the importance of performing high quality CPR immediately after a cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…With better implementation of the links of this chain, cardiac arrest survival can be improved. 6 Early and high quality cardiopulmonary resuscitation (CPR) has been shown to greatly improve the survival rate of cardiac arrest victims, 7,8 as indicated by American Heart Association (AHA) guidelines changes from 2005 to date. [9][10][11] For this reason, the 2015 Guidelines for Cardiopulmonary Resuscitation stress the importance of performing high quality CPR immediately after a cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that EMS dispatcher instruction for CPR can double the bystander CPR rate 8. Rea et al 9. reported that both dispatch‐assisted CPR (DACPR) and bystander CPR without dispatcher assistance are associated with improved survival for CA patients when compared to no bystander CPR.…”
Section: Introductionmentioning
confidence: 99%
“…Since Carter et al 8. proposed that a CPR instruction to give five ventilations and chest compressions for 5 min should be given to a bystander by telephone in 1984, many reports have suggested that dispatchers are able to diagnose cardiac arrest over the telephone accurately, and dispatchers’ oral guidance may increase chest compressions by bystanders and improve patients’ outcomes 9, 10, 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%